Insights into EPR Effect versus Lectin‐mediated Targeted Delivery: Biodegradable Polycarbonate Micellar Nanoparticles with and without Galactose Surface Decoration. Issue 21 (4th August 2014) - Attia, Amalina Binte Ebrahim; Oh, Pamela; Yang, Chuan; Tan, Jeremy Pang Kern; Rao, Nithya; Hedrick, James L.; Yang, Yi Yan; Ge, Ruowen
<x xml:space="preserve">Abstract</x> Polymeric micelles with and without galactose are synthesized to study liver targeting ability in an orthotopic HCC rat model. Micelles with galactose accumulate more in the healthy liver tissue instead of HCC, while micelles without galactose amass in HCC by the EPR effect. These micelles show great potential as drug delivery carriers to target either the liver or HCC. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>